India As Source Of Spirituality In Eat Pray Love Movie Directed By Ryan Murphy(2010): A Sosiological Approach - WIDYANTI, AMITA DWI (2012)
This study is aimed to show India as source of spirituality in Eat Pray Love movie directed by Ryan Murphy (2010) using Sosiological Approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing India as source of spirituality in Eat Pray Love movie based on sociological approach. Sociological theory based of Swingewood and Laurenson. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is Eat Pray Love movie directed by Ryan Murphy (2010). While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly,based on the structural analysis indicated that each of narrative elements and structural elements of movie have been related into solid unity. Secondly, based on sociological approach the researcher divides the aspects into six aspects whichconsists of social aspect, economic aspect, political aspect, cultural aspect, science and technology aspect, and religious aspect.